Associations of mucosal nerve fiber innervation density with Hirschsprung-associated enterocolitis: a retrospective three-center cohort study - Mösch, Michèle; Usemann, Jakob; Bruder, Elisabeth; Romero, Philipp; Schwab, Constantin; Niesler, Beate; Tapia-Laliena, María Angeles; Khasanov, Rasul; Nisar, Tauseef; Holland-Cunz, Stefan; Keck, Simone (European journal of pediatric surgery, 2023)
Objective Hirschsprung's disease (HSCR) is a congenital intestinal neurodevelopmental disorder characterized by the absence of enteric ganglion cells in the distal colon. Although Hirschsprung-associated enterocolitis (HAEC) is the most frequent life-threatening complication in HSCR, to date reliable biomarkers predicting the likelihood of HAEC are yet to be established. We established a three-center retrospective study including 104 HSCR patients surgically treated between 1998 and 2019. Materials and Methods Patient-derived cryopreserved or paraffin-preserved colonic tissue at surgery was analyzed via βIII-tubulin immunohistochemistry. We subsequently determined extrinsic mucosal nerve fiber density in resected rectosigmoid specimens and classified HSCR patients accordingly into nerve fiber-high or fiber-low groups. We compared the distribution of clinical parameters obtained from medical records between the fiber-high (n= 36) and fiber-low (n = 68) patient groups. We assessed the association between fiber phenotype and enterocolitis using univariate and multivariate logistic regression adjusted for age at operation. Results Enterocolitis was more prevalent in patients with sparse mucosal nerve fiber innervation (fiber-low phenotype, 87%) compared with the fiber-high phenotype (13%; p = 0.002). In addition, patients developing enterocolitis had a younger age at surgery (3 vs. 7 months; p = 0.016). In the univariate analysis, the odds for enterocolitis development in the fiber-low phenotype was 5.26 (95% confidence interval [CI], 1.67-16.59; p = 0.005) and 4.01 (95% CI, 1.22-13.17; p = 0.022) when adjusted for age. Conclusion Here, we showed that HSCR patients with a low mucosal nerve fiber innervation grade in the distal aganglionic colon have a higher risk of developing HAEC. Consequently, histopathologic analysis of the nerve fiber innervation grade could serve as a novel sensitive prognostic marker associated with the development of enterocolitis in HSCR patients.
Artikel online veröffentlicht: 14. Oktober 2022
Gesehen am 09.07.2024
Verlagslink funktioniert nicht